Study on Self-Compassion and Rumination among Working and Non-Working Diabetic Women - M. S. Sujamani; S. Usharani; B. Pooja (Emerging Trends in Disease and Health Research Vol. 3, 2022)
Objective: Diabetes that frequently impairs the physical ability and psychological difficulties among diabetic patients which accompanied by increased sufferings and compromised quality of life. Diabetes is a complex disease which requires evaluation of behavior- feeling compassion about oneself which is essential to self-management. The present research study describes how self-compassion offer supplementary framework for the improved management of diabetes among working and non-working women by providing protection against rumination and its downstream effects. Self-compassion suppresses the role of rumination and alleviates depression. Methods: Survey research design was adopted for this present study. Sample of (N=218) 109 Working and 109 non-working women with Purposive sampling method was used for this research. Data was collected using Self-Compassion Scale (SCS) developed by Kristen Neff and Ruminative Responses Scale (RRS) developed by Treynor, Gonzalez and Nolen- Hoeksema (2003). The data obtained were calculated by using Descriptive statistics ‘t’-test and Pearson’s correlation of co-efficient method. Results: Results shows that there was a strong negative correlation between rumination and self-compassion among working and non-working diabetic women and no significant difference between working and non-working diabetic women on self-compassion and rumination. Conclusion: Self-compassion acts as a buffering effect during adverse situation and repetitive thinking and protect from negative experience of rumination.